Short-distance quantum teleportation scheme for arbitrary unknown three-dimensional two-qutrit states - PENG Jiayin; LIU Miao; TANG Jiangang; XIANG Yi (Shenzhen Daxue xuebao. Ligong ban)
A new scheme for short-distance quantum teleportation of an arbitrary unknown three-dimensional two-qutrit state is proposed, utilizing a three-dimensional Bell-state and a ground-state auxiliary qutrit as quantum channel. In this scheme, both the sender and receiver are required to pre-share an auxiliary qutrit in addition to sharing the three-dimensional Bell state. The sender performs joint measurements on their Bell qutrit and the unknown quantum system after performing quantum gate operations on the auxiliary qutrit, and sends the classical information of the measurement results to the receiver. Based on the measurement results, the receiver converts, with 100% probability, the quantum state of his/her own Bell qutrit and auxiliary qutrit into an exact replica of the unknown quantum state initially altered by the sender. This scheme exhibits advantages such as a short transmission distance, high information capacity, reduced consumption of entanglement resources, and promising applications in quantum teleportation for solid-state devices, such as on-chip implementations.